Verifying the moderating role of satisfaction on service quality and students’ accomplishment in ODL perspective - Maximus Gorky Sembiring; Gayuh Rahayu (AAOU Journal, 2019)
Purpose – Service quality and satisfaction in the ODL setting related to students’ accomplishments (performance, loyalty and career) were reconsidered. It was aimed at exposing the moderating role of satisfaction on service quality and accomplishment. It was also of interest to scrutinize how, in what routines determinants engaged interdepended. The paper aims to discuss these issues. Design/methodology/approach – This study utilized an exploratory design. It was qualitatively identified first that service quality included tangible, empathy, assurance, reliability, responsiveness and referral factors. It preceded to satisfaction (perceived from academic, operational and managerial attitudes). Satisfaction led to accomplishment. Quantitatively, service quality, satisfaction and accomplishment were identified as independent, moderating, and dependent variables, respectively. Respondents, 500 Universitas Terbuka graduates, were randomly pursued to accumulate data by a survey. Methodically, importance-performance analysis (IPA) and customer-satisfaction index (CSI) were used to figure out satisfaction and their importance degree. Nine hypotheses were developed and examined using structural-equation modeling to visualize the loading factors. Findings – Replies from 163 respondents were completed. Seven of nine hypotheses were validated. It was distinguished that reliability influencing satisfaction, they were empathy, assurance and responsiveness; excluding tangible and referral. Satisfaction influenced performance, career, and loyalty. IPA-CSI analysis recognized 15 (of 21) attributes as the pillars of service quality. Originality/value – Despite the qualitative framework was improperly approved by quantitative procedure, they were methodically reliable. It was supported by the fact that nine cut-off values of goodness-of-fit requirements harmonized. Additional inquiry is therefore required to tail off variances by integrating a more appropriate approach, amplifying theoretical coverage, and/or extending population/sample size.